2014
DOI: 10.1016/j.prevetmed.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Infection-interactions in Ethiopian village chickens

Abstract: Chickens raised under village production systems are exposed to a wide variety of pathogens, and current or previous infections may affect their susceptibility to further infections with another parasite, and/or can alter the manifestation of each infection. It is possible that co-infections may be as important as environmental risk factors. However, in cross-sectional studies, where the timing of infection is unknown, apparent associations between infections may be observed due to parasites sharing common ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 36 publications
2
42
1
Order By: Relevance
“…Previous AnGRs valuation studies, in developing countries, also reported similar results (see Faustin et al., ; Kassie et al., ; Ouma et al., ). Farmers’ WTP higher for disease‐resistant chickens is justifiable, given chicken infectious diseases are widespread and animal health service is very limited in Ethiopia (Bettridge et al., ; Terfa, Garikipati, Kassie, Bettridge, & Christley, ). The WTP estimates also revealed that farmers are willing to pay a premium that is ETB 15.34 for chickens that had good meat and egg taste, compared with poor meat and egg taste, everything else kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…Previous AnGRs valuation studies, in developing countries, also reported similar results (see Faustin et al., ; Kassie et al., ; Ouma et al., ). Farmers’ WTP higher for disease‐resistant chickens is justifiable, given chicken infectious diseases are widespread and animal health service is very limited in Ethiopia (Bettridge et al., ; Terfa, Garikipati, Kassie, Bettridge, & Christley, ). The WTP estimates also revealed that farmers are willing to pay a premium that is ETB 15.34 for chickens that had good meat and egg taste, compared with poor meat and egg taste, everything else kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…Yet the ecology of MDV is poorly understood. This is perhaps most clearly exemplified by the conventional wisdom that the virus is ubiquitously found on industrialized poultry farms (Office International des-Epizooties, 2010; Dunn, 2013), despite recent surveillance data suggesting that the virus may not be present on a large fraction of farms (Groves et al, 2008; Wajid et al, 2013; Walkden-Brown et al, 2013; Bettridge et al, 2014; Kennedy et al, 2015b, 2017; Ralapanawe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Poultry industry is one of the major components of the Nigerian economy, serving as a source of income for farmers and a main source of high quality protein for the ever-growing population in Nigeria, due to their affordability and acceptability (Fagbamila et al, 2010;Bettridge et al, 2014). Poultry production plays an important role in the provision of animal protein, this account for about 25% of local meat production in Nigeria (Agbaje et al, 2010).…”
Section: Introductionmentioning
confidence: 99%